Uji Aktivitas Antidiabetes Ekstrak Etanol dari Akar dan Batang Tumbuhan Sekunyit (Fibraurea Tinctoria Lour) - Utami, Rahayu; Sandi, Nofri Hendri; Hasti, Syilfia; Delvia, Sutri (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X)
Sekunyit (Fibraurea tinctoria Lour) is a species plant that has been used as traditional medicine for treating several diseases including jaundice, dysentery, headache, eye infection as well as anti diabetic drug. This research aims to evaluate antidiabetic activity of ethanol extract of roots and stem of sekunyit on white male mice (Mus musculus L) using glibenclamide as positive control. The experimental animals were induced with alloxan 175 mg/Kg BW i.p and devided into six groups, each group consisted of five mice. Group one served as negative control which was given NaCMC 1%, group second was positive control, given  glibenclamide 0,65 mg/KgBW, while group third, fourth, fifth were administered orally with etanol extract with doses of 100, 200 and 300 mg/KgBW, respectively. The observed parameter were measurement of blood glucose levels, urine volume and volume of drinking water as well as ratio of relative organ weight. The treatment was conducted for 15 days. The result showed that administration of ethanol extract of roots and stem of sekunyit can lowered significantly blood glucose levels (p<0,05) of alloxan induced-diabetic mice, decreased urine volume (p<0,05), decreased volume of drinking water (p<0,05), and did not affect relative organ weight of heart, liver and kidney (p>0,05).